Influenza virus vaccine efficacy based on conserved sequence alignment - Baby Jerald, A.; Nair, T. R. Gopalakrishnan (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/